Effect of tooth loss on masticatory muscle pain of patients with bruxism (Annals of Medical Research, 2021)
Aim: It was aimed to compare the patients’ masticatory muscle pain according to the gender, side of the face with pain, muscle tenderness, and tooth loss.Material and Methods: The patients were selected randomly and the data were collected from 109 patients aged 18-50 years. Patients were examined by a maxillofacial surgeon and a prosthodontist blindly. During intraoral examination grinding, clenching confirmed by sleep partners or roommates, hyperkeratosis of cheek mucosa (linea alba), indented tongue, the unilateral masseter muscle hypertrophy, tooth wear, hypersensitivity, pain and fatigue in the chewing muscles in the daytime or in the morning were recorded. To classify tooth loss the Eichner index was used. It was asked to participants to score the masticatory muscle pain. Each participant scored the masticatory muscle pain on a visual analog scale (VAS/0-10). Data were analyzed with a non-parametric Mann-Whitney U test to compare the VAS results because the data were distributed non-normally. Chi-square test was used to compare categorical variables and Spearsman correlation test was performed to test the possible correlation between the masticatory muscle pain and age. Results: The percentage of bruxism in female (52.3%) was higher than in male (47.7%). A total of 15 patients (13.7%) had tooth loss (premolar or molar). Pain score was higher in patients with tooth loss than without tooth loss (p=0.49).Conclusion: The tooth loss may be increased the masticatory muscle pain. It should be considered both muscle pain and tooth loss together in clinical examination and perform the preventive treatment.
Keywords: Bruxism; pain; tooth loss